2015
DOI: 10.1007/s12664-015-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy in cirrhosis: A prospective study to correlate conventional tests of coagulation and bleeding following invasive procedures in cirrhotics

Abstract: Deranged conventional coagulation parameters did not predict clinically significant bleeding in cirrhosis. Whenever indicated, any invasive procedure could be safely carried out in patients with cirrhosis without prior correction of coagulation abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
3
23
0
2
Order By: Relevance
“…Similarly, some prospective studies also showed that cirrhotic patients rarely developed major bleeding after invasive procedures and that the incidence of major bleeding after invasive procedures was 0%–2.3%. [ 10 11 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, some prospective studies also showed that cirrhotic patients rarely developed major bleeding after invasive procedures and that the incidence of major bleeding after invasive procedures was 0%–2.3%. [ 10 11 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathy was defined as INR ≥1.5 and/or PLT ≤50 × 10 9 /L. [ 11 13 20 ] Severe thrombocytopenia was defined as PLT ≤50 × 10 9 /L. [ 11 13 20 ] Major bleeding after invasive procedures was defined as overt bleeding or decrease in hemoglobin to less than 80 g/L after invasive procedures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 45 , 46 , 47 ] This results revealed the severity of the impairment and particularly the degree of neuromuscular inability of patients: thinking difficulties, problems with speaking fluently, guiding movements, memory alteration, and the appearance of tremors in their distal extremities. [ 4 , 6 , 48 , 49 , 50 , 51 ] In addition, H-R score with regards to genders showed that female patients in the study group were more psychologically and neurologically affected by HE when compared with male. [ 49 , 52 , 53 ]…”
Section: Discussionmentioning
confidence: 99%